THE ROLE OF SOCIAL MEDIA IN THE DEVELOPMENT OF INTERCULTURAL COMPETENCE AMONG UNIVERSITY STUDENTS IN AZERBAIJAN - Seva IMANOVA (Association of Social and Educational Innovation, 2022)
The paper deals with the issues of forming and developing students' intercultural competence (IC) level and the demands for culture-based, appropriate teaching materials including social websites in Azerbaijan. In order to succeed in fostering students' intercultural competence, the content and teaching strategies of foreign languages, all educational documents, programs, syllabi, and teaching materials must be thoroughly designed based on culture. The swift development of global economy, transportation, and communication necessitates the tendencies relating to intercultural competence meaning that people from multicultural backgrounds has made intercultural competence very relevant. In this context, social media play a key role in increasing the Internet users' culture awareness and improving intercultural competence. In this study, the questionnaire was designed in order to gain the influence of social media in the development of intercultural competence and the impacts of learning foreign languages among the students who study at Azerbaijan University of Languages. Using social media in the classroom environment contributes to understanding of foreign cultures which facilitates the language acquisition.